PROTEIN-SYNTHESIS IN RABBIT RETICULOCYTE LYSATES FREE OF HEMOGLOBIN - (:unkn) unknown (MBR PRESS INC, 1993)
The conditions under which the highest activity in rabbit reticulocyte lysates can be achieved have been studied by different investigators (1,2). Hemoglobin represents about 90% of the total protein in rabbit reticulocyte lysate. The effect of the absence of hemoglobin deserves thus clarification. The present study shows that the activity of protein synthesis in hemoglobin-free rabbit reticulocyte lysate is higher than that of the control lysate.
Keywords: SYSTEMS